Implementing Ecosystem-Based Management Principles in the Design of a Salmon Ocean Ecology Program - Wells, Brian K.; Huff, David D.; Burke, Brian J.; Brodeur, Richard D.; Santora, Jarrod A.; Field, John C.; Richerson, Kate; Mantua, Nathan J.; Fresh, Kurt L.; McClure, Michelle M.; Satterthwaite, William H.; Darby, Forbes; et al. (Frontiers in Marine Science, 2020)
Two decades have passed since the initiation of the National Oceanic and Atmospheric Administration’s research program aimed at advancing the understanding of estuary and ocean ecology of U.S. West Coast Pacific salmon (Oncorhynchus spp.). In this review and prospectus, we summarize key findings from this program and describe a plan for transitioning it to better support Ecosystem-Based Management (EBM). While we focus on salmon research, our approach applies to research design generally. Our path forward involves increasing understanding of ecosystem processes to improve the dependability of scenario testing under novel conditions. Over the past two decades, we developed a conceptual model for how climate, predators, prey, fisheries, and human activities influence salmon. Knowledge gaps we identified from our conceptual model include limited understanding of salmon distributions, behavior, maturation dynamics, and population dynamics, and salmon interactions with predators, competitors, and prey during winter. We consider emerging risks and vulnerabilities facing salmon and propose analysis frameworks for evaluating them. Increased predator populations, coupled with climate change, pose increasing threats to West Coast salmon and will require new strategies and actions to mitigate their negative impacts. We propose research to support the development of decision-support tools to evaluate tradeoffs associated with alternative management strategies and to inform an adaptive ecosystem management system to improve the resilience of salmon populations and salmon-dependent fisheries.